2017
DOI: 10.1038/s41467-017-00369-y
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine metabolism regulates autophagy-dependent mTORC1 reactivation during amino acid starvation

Abstract: Activation of autophagy and elevation of glutamine synthesis represent key adaptations to maintain amino acid balance during starvation. In this study, we investigate the role of autophagy and glutamine on the regulation of mTORC1, a critical kinase that regulates cell growth and proliferation. We report that supplementation of glutamine alone is sufficient to restore mTORC1 activity during prolonged amino acid starvation. Inhibition of autophagy abolishes the restorative effect of glutamine, suggesting that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(139 citation statements)
references
References 35 publications
(79 reference statements)
7
128
0
Order By: Relevance
“…The protective effect of Gln derives from its multiple roles in the cell as a metabolic fuel for mitochondrial anaplerosis, protein, nucleotide and fatty acid synthesis, reactive oxygen species homeostasis (Still & Yuneva, ), and Gln has the ability to regulate gene expression in a variety of cellular processes (Brasse‐Lagnel, Lavoinne, & Husson, ; Curi et al, ). More specifically, Gln has been shown to restore or stimulate mTORC1 (a central regulator of cell growth) activity during amino acid starvation (Chiu et al, ; Tan, Sim, & Long, ) and also via glutaminolysis (Durán et al, ). We recently reported that there was a clear trend towards increased exponential phase glutamine uptake associated with elevated exponential growth and fed‐batch culture performance of CHO‐S cells (Fernandez‐Martell, Johari, & James, ) and Tabuchi et al () reported that Gln consumption was increased in high‐yielding CHO‐DXB11 cells overexpressing the taurine transporter.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of Gln derives from its multiple roles in the cell as a metabolic fuel for mitochondrial anaplerosis, protein, nucleotide and fatty acid synthesis, reactive oxygen species homeostasis (Still & Yuneva, ), and Gln has the ability to regulate gene expression in a variety of cellular processes (Brasse‐Lagnel, Lavoinne, & Husson, ; Curi et al, ). More specifically, Gln has been shown to restore or stimulate mTORC1 (a central regulator of cell growth) activity during amino acid starvation (Chiu et al, ; Tan, Sim, & Long, ) and also via glutaminolysis (Durán et al, ). We recently reported that there was a clear trend towards increased exponential phase glutamine uptake associated with elevated exponential growth and fed‐batch culture performance of CHO‐S cells (Fernandez‐Martell, Johari, & James, ) and Tabuchi et al () reported that Gln consumption was increased in high‐yielding CHO‐DXB11 cells overexpressing the taurine transporter.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid catabolism is regulated by autophagy (Singh et al, 2009). Additionally, autophagy promotes cancer survival by recycling intracellular proteins and organelles under conditions like oxidative stress or deprivation of nutrients (Tan et al, 2017; White, 2012), thereby sustaining overall metabolic homeostasis (Mizushima and Komatsu, 2011). Here we showed that shift toward lipid catabolism, under inhibited glutaminolysis, observed in our study, was accompanied by increased oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine‐dependent regulation of autophagy is especially relevant in cancer cells which support their proliferation by increased uptake and catabolism of glutamine required as source of nitrogen and for anaplerosis . Glutamine generated by GS inhibits mTORC1 thus activating autophagy in cancer cells whereas sequential reactions catalyzed by glutaminase (GLS) and glutamate dehydrogenase (GDH) enzymes generate α‐KG from glutamine that stimulates mTORC1 and inhibits autophagy . Therefore, enhanced oxidative/proteotoxic stress induced by simultaneous inhibition of GLS (a source of glutathione) and heat shock protein 90 (HSP90) strongly induces programmed cell death in models of cancer driven by mTORC1 hyper‐activation .…”
Section: Glutamine and Autophagymentioning
confidence: 99%